2006
DOI: 10.1007/s10681-006-9160-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow from transgenic wheat and barley under field conditions

Abstract: In this study the frequency and distance of gene flow from transgenic wheat (Triticum aestivum) and barley (Hordeum vulgare) to non-transgenic wheat and barley crops was investigated under local field conditions. Trials were conducted in the Australian Capital Territory (ACT) and in South Australia (SA). Gene flow from transgenic wheat was confirmed at frequencies of 0.012% and 0.0037% in the ACT and SA, respectively. In both trials gene flow occurred over distances of less than 12 m. Gene flow was also detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…Although pollen-mediated gene flow has been studied in many crops including canola (Beckie et al, 2003;Knispel et al, 2008), maize (Messeguer et al, 2006;Goggi et al, 2007;Weber et al, 2007;Mercer and Wainwright, 2008), wheat (Gaines et al, 2007;Gatford et al, 2007;Matus-Cadiz et al, 2007), soybean (Yoshimura et Total number of seeds screened from all (eight) blocks for a specific distance from the pollen source. Value of power (1Àb) was calculated for 95% confidence interval (a ¼ 5%) using equation (1) …”
Section: Discussionmentioning
confidence: 99%
“…Although pollen-mediated gene flow has been studied in many crops including canola (Beckie et al, 2003;Knispel et al, 2008), maize (Messeguer et al, 2006;Goggi et al, 2007;Weber et al, 2007;Mercer and Wainwright, 2008), wheat (Gaines et al, 2007;Gatford et al, 2007;Matus-Cadiz et al, 2007), soybean (Yoshimura et Total number of seeds screened from all (eight) blocks for a specific distance from the pollen source. Value of power (1Àb) was calculated for 95% confidence interval (a ¼ 5%) using equation (1) …”
Section: Discussionmentioning
confidence: 99%
“…They supposed that unexpected variation of outcrossing rate among GM lines and original variety was evidently due to the different transgene insertion events. On the other hand Gatford et al (2006) reported extremely low transgene flow frequency from 0.0037 to 0.012 % in adjacent field plots. Despite the previous observation that single outcrosses could be found at considerable distance from the pollen donor, Foetzki et al (2012) found only a limited number of outcrosses within the border crop surrounded the GM wheat plot, however the experimental field was set up at a distance of 200 m.…”
Section: Introductionmentioning
confidence: 91%
“…In 1996-1998 transgenic wheat plants contained bar gene conferring the resistance to glufosinate-based herbicides were grown in South Australia and Australian Capital Territory (Gatford et al 2006). Several field trials involved transgenic wheat lines expressed two pathogenesis-related genes (chi, glu) and herbicide resistance gene (bar) were planted in Switzerland in 2008-2010(Riebien et al 2011Foetzki et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Golden Promise in south-eastern Australia. The results indicated that outcrossing occurred at a rate of 0.005 % over a distance of less than 12 m, and therefore, the risk of gene fl ow between transgenic and non-transgenic barley at the fi eld scale would be very low providing that crops were separated by a few metres (Gatford et al 2006 ).…”
Section: Field Trials and Risk Assessmentmentioning
confidence: 99%
“…Marker-free transgenic plants are one of the solutions to this issue (Matthews et al 2001 ;Xue et al 2003 ). Further, the gene fl ow between the transgenic barley and its wild counterpart also remains a concern despite careful investigations on this issue (Gatford et al 2006 ). Additionally, apprehensions with regard to possible health risks by consumption of end products from genetically modifi ed barley also exist thereby forcing the industry to take a wait-and-see stance.…”
Section: Public Acceptancementioning
confidence: 99%